2014
DOI: 10.3748/wjg.v20.i20.6081
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in the pre-operative treatment of locally advanced rectal cancer: A systematic review

Abstract: Despite advances in the management of patients with locally advanced, non-metastatic rectal adenocarcinoma (LARC), prognosis remains largely unsatisfactory due to a high rate of distant relapse. In fact, currently available neoadjuvant protocols, represented by fluoropyrimidine-based chemo-radiotherapy (CT-RT) or short-course RT, together with improved surgical techniques, have largely reduced the risk of local relapse, with limited impact on distant recurrence. Available results of phase III trials with addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Inevitably, for a portion of patients, that is, those with sphincter-infiltrating tumors, APR is still the only curative treatment. In the future, the application of preoperative, targeted therapy to nonmetastatic rectal cancer could further reduce the nearly stagnating rate [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inevitably, for a portion of patients, that is, those with sphincter-infiltrating tumors, APR is still the only curative treatment. In the future, the application of preoperative, targeted therapy to nonmetastatic rectal cancer could further reduce the nearly stagnating rate [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies about the combination of biologic agents and NCRT have been reported. Although the addition of bevacizumab showed a favorable pCR rate, it is considered to significantly increase toxicity, including enteritis or perforation, and surgical complications, including delayed wound healing, fistula, or bleeding [ 23 ]. A combination of cetuximab has shown disappointing pCR [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with previous long-term followup results, 8% of the patients had LR; however, the promising local control rates came at the expense of patients' urinary, bowel, and stoma functions. Pursuant to this, the investigators stressed the need for long-term follow-up that would allow for weighing the risks and benefits of targeted multimodality treatments for LARC, specifically the inclusion of patient-reported outcomes and predictors of long-term toxicity in future trials (33).…”
Section: Induction Chemotherapy Vs Consolidation Chemotherapy: Stratmentioning
confidence: 99%